2004
DOI: 10.1111/j.1439-0531.2004.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Oestrous Synchronization of Postpartum Dairy Cows with and without Ovarian Disorders

Abstract: This report reviews the most recent developments in prostaglandin-based oestrous synchronization programmes for postpartum dairy cows and addresses the efficiency of controlled breeding protocols based on such developments for cows with abnormal ovarian conditions. A double prostaglandin protocol applied 11-14 days apart seems to be capable of bringing most cows to oestrus. Because of varying oestrus onset times, improved conception rates are obtained following artificial insemination (AI) at detected oestrus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 90 publications
(175 reference statements)
0
37
0
2
Order By: Relevance
“…However, other studies revealed an increase in pregnancy rates in cows treated with 10 -250 µg of GnRH analog in the diestrus period (at the time of AI or 12 days after AI) (Macmillan et al 1986;Lajil et al, 1991, Lopez-Gatiuz et al, 2006. According to Thatcher et al (1989), Chenault et al (1990) and Yániz et al (2004), the positive effect of…”
Section: Resultsmentioning
confidence: 99%
“…However, other studies revealed an increase in pregnancy rates in cows treated with 10 -250 µg of GnRH analog in the diestrus period (at the time of AI or 12 days after AI) (Macmillan et al 1986;Lajil et al, 1991, Lopez-Gatiuz et al, 2006. According to Thatcher et al (1989), Chenault et al (1990) and Yániz et al (2004), the positive effect of…”
Section: Resultsmentioning
confidence: 99%
“…ovsynch) regulate ovarian functions and hence sexual cycles Tenhagen et al, 2004;Yàniz et al, 2004) and as a result the number of inseminations per pregnancy decreases (Tóth et al, 2006). The present study has also determined a decrease, though insignificant, in the number of inseminations per pregnancy following presynch-ovsynch protocol.…”
mentioning
confidence: 69%
“…In anovulatory anestrus, exogenous progesterone applications can be very useful [84]. The use of intravaginal progesterone devices, such as PRID or CIDR, may induce the restart of cyclic activity in the ovary [13].…”
Section: Use Of Progesterone In Anestrus or Anovulatory Anestrusmentioning
confidence: 99%